SYSTEM FOR EVALUATING THE ENERGY EFFICIENCY OF SYNCHRONIZED ACCESS IN A SIMULATION MODEL OF A WIRELESS SENSOR NETWORK - S. V. Kapustin; R. F. Khalabia (Современная наука и инновации, 2022)
The article examines the energy efficiency of nodes in the structure of a simulated model of synchronized access of a wireless sensor network, provides rationale and evidence for the use of simulation based on the Time Division Multiple Access (TDMA) method, to evaluate reliability, an algorithm is used to determine the f path of a node to a base station at the lower boundary of stability assessment. The main task of the investigated synchronized access of the data link layer is to configure the protocol temporal parameters. The proposed simulation model corrects defects in the network specification and estimates the volume at the time of transmission and per unit of time at an early stage of network architecture setup. The main advantage of the simulation model is the high energy efficiency of the wireless sensor nodes when deploying a wireless sensor network.